Covered stents for exclusion of iatrogenic common carotid artery–internal jugular vein fistula and brachiocephalic artery pseudoaneurysm. (23rd June 2015) - Kooraki, Soheil; Grohmann, Jochen; Elshikh, Samer; Urbach, Horst; Meckel, Stephan
Abstract : Covered stents have rarely been used in neuroendovascular procedures. We report the case of a 74-year-old woman with a complex iatrogenic vascular injury from attempted insertion of a hemodialysis catheter: concurrent brachiocephalic artery pseudoaneurysm and common carotid artery to internal jugular vein fistula. Both lesions were excluded successfully by using two balloon-expandable covered stents with a satisfactory short-term clinical and angiographic outcome.